Smartband Use During Enhanced Recovery After Surgery Facilitates Inpatient Recuperation Following Minimally Invasive Colorectal Surgery - Yin, Tzu-Chieh; Huang, Ching-Wen; Tsai, Hsiang-Lin; Su, Wei-Chih; Ma, Cheng-Jen; Chang, Tsung-Kun; Wang, Jaw-Yuan (Frontiers in Surgery, 2021)
Background Enhanced recovery after surgery (ERAS) is valuable in perioperative care for its ability to improve short-term surgical outcomes and facilitate patient recuperation after major surgery. Early postoperative mobilization is a vital component of the integrated care pathway and is a factor strongly associated with successful outcomes. However, early mobilization still has various definitions and lacks specific strategies. Methods Patients who underwent minimally invasive surgery for colorectal cancer followed our perioperative ERAS program, including mobilization from the first postoperative day. After perioperative care skills were improved in our well-established program, compliance, inpatient surgical outcomes, and complications associated with adding smartband use were evaluated and compared with the outcomes for standard protocol. Quality of recovery was evaluated using patient-rated QoR-40 questionnaires the day before surgery, on postoperative day 1 and 3, and on the day of discharge. Results Smartband use after minimally invasive colorectal surgery failed to increase compliance with early mobilization or reduce the occurrence of postoperative complications significantly compared with standard ERAS protocol. However, when smartbands were utilized, quality of recovery was optimized and patients returned to their preoperative status earlier, at postoperative day 3. The length of hospital stay, as defined by discharge criteria, and hospital stay of patients without complications was reduced by 1.1 and 0.9 days, respectively (P = 0.009 and 0.049, respectively). Conclusions Smartbands enable enhanced communication between patients and surgical teams and strengthen self-management in patients undergoing minimally invasive colorectal resection surgery. Accelerated recovery to preoperative functional status can be facilitated by integrating smartbands into the process of early mobilization during ERAS.